2018
DOI: 10.3201/eid2404.172131
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Dengue Fever Imported from Egypt to Russia, 2017

Abstract: In 2017, two cases of dengue fever were imported from Hurghada, Egypt, where dengue fever was not considered endemic, to Moscow. These cases show how emergence of dengue fever in popular resort regions on the coast of the Red Sea can spread infection to countries where it is not endemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
0
7
0
1
Order By: Relevance
“…aegypti was reintroduced and reestablished [ 21 ]. Two cases of dengue fever were reported in travelers returning to Moscow, Russia, from the Red Sea coast of Egypt in the same year [ 20 ]. In 2019, the seropositivity rate for DENV antibodies in the population under the age of 21 years was 25%, although the rate was determined based on a limited sample size ( n = 8) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…aegypti was reintroduced and reestablished [ 21 ]. Two cases of dengue fever were reported in travelers returning to Moscow, Russia, from the Red Sea coast of Egypt in the same year [ 20 ]. In 2019, the seropositivity rate for DENV antibodies in the population under the age of 21 years was 25%, although the rate was determined based on a limited sample size ( n = 8) [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, a DENV resurgence occurred in the Dairoute District of the Assyoute (Assiut) Governorate, with at least 253 cases [ 18 , 19 ]. In 2017, two cases of DENV were reported in travelers returning to Moscow, Russia, from Hurghada, Egypt, on the Red Sea coast [ 20 ]. In the same year, a DENV outbreak with at least 680 cases occurred in the Red Sea Governorate, where the reintroduction and breeding of Ae.…”
Section: Introductionmentioning
confidence: 99%
“…Five years later, an outbreak occurred in humans residing in Dariot district, Asyut Governorate; however, it was rapidly contained after application of the appropriate control measures [ 14 ]. Recently, in 2017, up to 2500 human cases of DF disease were reported in the Red Sea Governorate [ 15 ] where A. aegypti was documented to be circulating [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In October 2017, the health department of the Red Sea Governorate reported cases of dengue fever in El-Qoseir City 145 km south of Hurghada, with a population of about 50,000. The preliminary results suggested that 1,200-2,500 persons were infected (El-Sheikh, 2017;Saifullin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%